Pendampingan Anak Migran Indonesia dalam Penulisan Karya Tulis di PKBM PNF KBRI Kuala Lumpur Malaysia - Syukrillah, Achmad; A yun, Qurroti; Mahsun, Moch; Syuhud, Syuhud; Darwis, Mohammad; Idris, Haidar (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Indonesian migrant children studying at PKBM PNF KBRI Kuala Lumpur face various challenges in accessing education, particularly in developing writing literacy skills. The unstable socio-economic conditions of migrant worker families and the limited learning facilities often hinder their learning process. Based on observations at the Community Learning Center (PNF) KBRI Kuala Lumpur, it was found that most students still struggle to write simple sentences and are not yet accustomed to expressing ideas in written form. This mentoring program aims to improve the writing literacy skills of migrant children through the Writing Assistance Program for Migrant Children at PNF KBRI Kuala Lumpur. The strategy used is Service Learning with a participatory-educative approach, in which university students act as facilitators who guide learners actively and reflectively. The implementation of the program includes problem identification, planning, implementation, reflection, and follow-up stages. Data were collected through observations, interviews, and documentation of students’ writing products throughout the activity. The results show an improvement in learners’ basic writing abilities, including increased confidence, better understanding of sentence structure, and improved neatness. Students also demonstrated positive attitudes toward writing activities and greater confidence in expressing themselves through written text. Contextual approaches and the use of simple media were proven effective in creating an active and enjoyable learning atmosphere. Thus, this mentoring program not only contributes to enhancing the writing literacy skills of migrant children but also strengthens the application of the Service Learning concept in community service. The program serves as a reciprocal learning space between university students and learners and offers inspiration for implementing literacy mentoring in other non-formal education settings.